2004
DOI: 10.1116/1.1722506
|View full text |Cite
|
Sign up to set email alerts
|

Optical switching of vanadium dioxide thin films deposited by reactive pulsed laser deposition

Abstract: The parameters of reactive pulsed laser deposition were successfully optimized for fabrication of vanadium dioxide thin films. It is observed that the O2 concentration in Ar gas and the total deposition pressure are critical in stabilizing the single VO2 phase. Thermochromic VO2 and V1−xWxO2 (x=0.014) thin films were synthesized on various substrates (silicon, quartz, and sapphire) at 5% of O2/Ar ratio gas and total pressure of 90 mTorr. The structural properties of the deposited films were analyzed by x-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 24 publications
1
67
0
Order By: Relevance
“…The details of deposition conditions and the switching characteristics of these layers were reported in previous publications [6,7]. Standard photolithography followed by plasma etching was used to pattern the layers into planar micro-switches (100 µm wide by 1000 µm long).…”
Section: Methodsmentioning
confidence: 99%
“…The details of deposition conditions and the switching characteristics of these layers were reported in previous publications [6,7]. Standard photolithography followed by plasma etching was used to pattern the layers into planar micro-switches (100 µm wide by 1000 µm long).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, two samples of VO 2 coating were deposited on aluminum alloy substrates using laser ablation deposition technic [4]. Metallic vanadium target was used.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Coating can be deposited on different substrates using various methods including chemical vapor deposition [6], electron beam evaporation [7], RF sputtering [8], sol-gel technique [9], and pulsed laser vacuum deposition [10]. A recent works by Kruzelecky et al [11] and Soltani et al [4] demonstrated that a tuneability of ∼60% in emissivity of VO 2 coating can be achieved by proper control of the stoichiometry and microstructure of the coating. However, there is a concern if space environment, particularly the atomic oxygen, would degrade the performance of the coating.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…SMPT and electrical switching determine the use of vanadium dioxide in temperature sensors, optical switches, memory elements, energy-saving coatings for glass, optical information carriers, and thermochromic indicators [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%